2021
DOI: 10.1016/j.ijrobp.2020.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Proton Therapy for Pediatric Patients: Improving the Quality of the Delivered Plan With On-Treatment MRI

Abstract: Pencil-beam scanning proton therapy is particularly sensitive to anatomic changes, which may negatively affect plan quality. We hypothesized that magnetic resonance imaging (MRI)-based adaptation can improve plan quality for pediatric patients. By evaluating 230 MRI scans acquired in treatment position during proton therapy, we found that onefourth of patients exhibited anatomic change, more than half of which result in suboptimal delivered plans. This highlights the potential role for MRI-guided proton Purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…We have previously described our offline MRI-guided adaptive proton therapy workflow [ 1 ]. During proton therapy, patients undergo offline MRI tx to detect anatomic changes that affect delivery accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described our offline MRI-guided adaptive proton therapy workflow [ 1 ]. During proton therapy, patients undergo offline MRI tx to detect anatomic changes that affect delivery accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…The enhanced-dose sculpting capability of pencil-beam scanning proton therapy is associated with increased sensitivity to anatomic changes. Although 27% of pediatric patients demonstrate anatomic changes during therapy, current treatment planning methods do not effectively account for anatomic variation [ 1 ]. This could potentially result in suboptimal delivered plans, defined as inadequate coverage of tumor or increased dose to healthy structures.…”
Section: Introductionmentioning
confidence: 99%
“…Data by Merchant et al have demonstrated the important role of weekly MR surveillance examinations in children with craniopharyngioma receiving RT to allow for re-planning in the case of cystic change during the course of treatment [34] . Similarly, ad hoc offline MR may be used to inform the need for proton re-planning in pediatric patients with intracranial or extracranial tumors [35] . However, cystic changes occurring in between MRI examinations can be missed for a number of fractions, hence the potential benefit of daily MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-fraction anatomical changes include tumour motion [41,42], tumour target volume change (due to tumour growth, regression or change in oedema) [43][44][45], and changes in position of normal organs, all of which affect tissue density within the beam path resulting in range uncertainties and issues with tumour coverage. These inter-fraction changes are better detected on MRI than X-ray imaging.…”
Section: Mri-guided Proton Therapy -Advantages For Assessing Inter-fr...mentioning
confidence: 99%
“…These inter-fraction changes are better detected on MRI than X-ray imaging. A paediatric cancer study assessing MRI detected anatomical changes during proton therapy found that 27% of paediatric patients had anatomical changes in their gross tumour volume or in the tissue density within the beam path, and over half of these resulted in a significant deterioration in plan quality [45]. Rhabdomyosarcomas and low grade gliomas had the highest rate of anatomical change at 100% and 24%, respectively.…”
Section: Mri-guided Proton Therapy -Advantages For Assessing Inter-fr...mentioning
confidence: 99%